The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.22270/jddt.v10i6.4545
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Trends in the Burden of Cardiovascular Diseases in the Southeast Region of Nigeria

Abstract: Background and Objective: Cardiovascular diseases (CVDs) are leading causes of non-communicable diseases and are increasingly becoming the major causes of morbidity and mortality in Nigeria. Published literature on the changing patterns and outcome of CVD admissions in the southeast region of Nigeria is scanty. This study, therefore, set out to bridge this gap in knowledge. Subjects and Methods: This was a 10-year retrospective descriptive study in which data about patients admitted on account of the CVD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The high rate of obesity led to an increase in non-communicable diseases (NCDs) such as diabetes mellitus (WHO, 2020). Estimated 5.8% (n= 6 million) of Nigerians adults were diagnosed with diabetes mellitus in 2018 with a consequential impact on the mortality rate [10]. According to the WHO (2021), NCDs accounted for nearly 30% of all deaths in Nigeria of which 3% related to diabetes and 12% CVD [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high rate of obesity led to an increase in non-communicable diseases (NCDs) such as diabetes mellitus (WHO, 2020). Estimated 5.8% (n= 6 million) of Nigerians adults were diagnosed with diabetes mellitus in 2018 with a consequential impact on the mortality rate [10]. According to the WHO (2021), NCDs accounted for nearly 30% of all deaths in Nigeria of which 3% related to diabetes and 12% CVD [11].…”
Section: Introductionmentioning
confidence: 99%
“…Nigerian males were more occupied with work during the day and consumed less meals. Also, the work stimulated the males being physically active, burned calories effectively and thereby prevented weight gain[10]. For those reasons, the study showed the number of Nigerian males diagnosed with obesity was lower than in females[2].…”
mentioning
confidence: 99%